Psychotherapeutic Methods of Coping with Stress in Everyday Life - Senol TURAN; Cana AKSOY POYRAZ (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Stress is an inevitable part of life. Knowing the ways of coping with stress are necessary to preserve our mental and physical health and to maintain good social and/or occupational functioning in daily life activities. Different ways of coping with stress have been developed throughout history. Various type of therapies offer quite effective remedies for coping with stress in everyday life. Among psychotherapeutic treatments cognitive behavioral therapy which involves teaching stressful individuals to develop coping strategies have yielded very promising results. It is helpful to determine first whether stress source can be changed, several therapeutic approaches may then be used. Lazarus and Folkman have identified two major approaches for coping with stress so-called "problem-focused" and "emotion-focused". In "problem-focused" approaches targets are acquiring time management, self-monitoring, problem-solving skills, while in "emotion-focused" approaches, through ways of accepting or rejecting of stress associated negative emotions, or reconciling with these emotions, the target is learning how to keep emotions under control. "Problem-focused" and "emotion-focused" approaches may independently be used effectively in appropriate cases, their simultaneous practice may increase chances of successful treatment. Apart from this methods, psychodynamic therapy may be indicated in some cases. [JCBPR 2015; 4(3.000): 133-140]